Control of near-infrared dye fluorescence lifetime in all-polymer microcavities. (1st August 2022) - Megahd, Heba; Villarreal Brito, Mariela; Lanfranchi, Andrea; Stagnaro, Paola; Lova, Paola; Comoretto, Davide
Abstract : The authors demonstrate photoluminescence lifetime and intensity control in a near-infrared dye embedded in all-polymer microcavity. Abstract : The control of radiative decay rate is a crucial issue both for fundamental studies in quantum electrodynamics and for the development of efficient lasers, light emitting devices and photovoltaic cells. In this paper we investigate the integration of a near-infrared molecular fluorophore in an all-polymer planar microcavity. Subsequently, we report the modulation of the fluorescence decay and radiative rate of the dye used and, in addition, of its fluorescence spectral line-shape and intensity. These effects have been possible through engineering the dielectric contrast of the polymers used to grow the flexible dielectric mirrors, thus blazing a trail to innovative opportunities for invisible near-infrared-light communications and wireless technologies.